PENGARUH CURAH HUJAN, HARI HUJAN, DAN DRY SPELL TERHADAP PERODUKTIVITAS KELAPA SAWIT (Elaeis guineensis Jacq) DI AFDELING I KEBUN AEK TOROP PT. PERKEBUNAN NUSANTARA III - Manurung, Saroha; Djaingsastro, Aulia Juanda; Siburian, Samura Natanael (Fakultas Pertanian, Universitas Janabadra, 2024)
Rainfall is high every year, ranging from 2000 – 2500 mm/year and evenly distributed throughout the year. Falling rain will cause the successive opening of leaves that have not yet bloomed, resulting in the formation of leaves which will then stimulate the formation of flowers. Thus, sufficient rainfall in terms of quantity and distribution will cause oil palm plants to be able to produce optimally. This research method uses SPSS Windows 25, namely Multiple Linear Regression and Correlation analysis. Where the significant value of the influence of rainfall (X1) on productivity (Y) is 0.912 with a correlation value of 0.046. The significant value of rainy days (X2) on productivity (Y) is 0.967 with a correlation value of 0.267. The significant value of the effect of dry spell (X3) on productivity (Y) is 0.609 with a correlation value of 0.457. With the results of this research, the influence of rainfall, rainy days and dry spell on palm oil productivity has a positive effect and has sufficient correlation with productivity